The Impact of Gold and Silver Nanoparticles on The DNA Yield of Mycobacterium Tuberculosis MTB - Zaid Mohammed Joodi Al- Janabi1 , Arshed H.Yaseen2 , Raghad Abdullah Hassan3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The objective of this research study whether nanoparticles of gold (Au NP) and nanoparticles silver (Ag NP)have an effect on the yield of DNA from Mycobacterium tuberculosis (MTB) in this experiment when it wasextracted DNA from MTB using gold and silver nanoparticles at different concentrations (l0?l, 50?l and100?l) then showed a significant impact on the yield of DNA, especially gold nanoparticles compared withDNA extracted without any of the nanoparticles.by Using a graph obtained from the REALTIME qPCR,which became very clear when the control sample (MTB without any nanoparticles) showed a high value forthe Ct (cycle threshold), which meant that low quantities of DNA. While samples containing nanoparticleswere low in Ct which meant a high yield of DNA was shown. Ct values also decreased when the concentrationof nanoparticles increased, eventually we conclude from the above experiment that nanoparticles showedhigh yield of MTB DNA. These results are likely due the interaction of the nanoparticles utilized with thecell wall and cell membrane of bacterium, which has facilitated the yield of DNA. Further refinement can beto the above said method and the nanoparticles could possibly use as an effective component of Nucleic acidextraction kits for molecular diagnosis and research so that a superior yield is obtaine.